2(x-3)-5=9(b+2)+1

Simple and best practice solution for 2(x-3)-5=9(b+2)+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x-3)-5=9(b+2)+1 equation:


Simplifying
2(x + -3) + -5 = 9(b + 2) + 1

Reorder the terms:
2(-3 + x) + -5 = 9(b + 2) + 1
(-3 * 2 + x * 2) + -5 = 9(b + 2) + 1
(-6 + 2x) + -5 = 9(b + 2) + 1

Reorder the terms:
-6 + -5 + 2x = 9(b + 2) + 1

Combine like terms: -6 + -5 = -11
-11 + 2x = 9(b + 2) + 1

Reorder the terms:
-11 + 2x = 9(2 + b) + 1
-11 + 2x = (2 * 9 + b * 9) + 1
-11 + 2x = (18 + 9b) + 1

Reorder the terms:
-11 + 2x = 18 + 1 + 9b

Combine like terms: 18 + 1 = 19
-11 + 2x = 19 + 9b

Solving
-11 + 2x = 19 + 9b

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '11' to each side of the equation.
-11 + 11 + 2x = 19 + 11 + 9b

Combine like terms: -11 + 11 = 0
0 + 2x = 19 + 11 + 9b
2x = 19 + 11 + 9b

Combine like terms: 19 + 11 = 30
2x = 30 + 9b

Divide each side by '2'.
x = 15 + 4.5b

Simplifying
x = 15 + 4.5b

See similar equations:

| 4(2x-5)=32 | | e+7e= | | -5x-15=-9 | | -9x-136=307 | | -75=6+9x | | 6(4t+1)-14=t-(t-7) | | 9x-5=2x+9 | | -14+6b+7=-8x-8 | | 3x-8=5x-(x+4) | | -7x+-2=-76 | | 4a-7a-13a= | | -6(x+6)+7(2x+1)= | | 3(p-3)=2(2p+1) | | 54-9x=18 | | -3x^4+12x^3+15x^2+108x-108=0 | | 3x+15=6(x-6) | | 8x-7=3x-4 | | .20(12)+.05x=.10(24+x) | | 7x+3=15x-29 | | 14x+16=44 | | 3y+2=y-5 | | 37n=-222 | | 12x-8=44 | | xa-x=c | | 3-2a=3a-1 | | 3(r+8)-r=(5-r) | | r=4h+4z | | -100+30x+30x^2+30x^3+30x^4+30x^5=0 | | -15y=150 | | x+5=-17 | | 12(n+1)=15n-6 | | x^4-2x^3+6x^2=0 |

Equations solver categories